Sample preparation for pesticide analysis in water and sediments a case study of the Okavango Delta, Botswana - Mmualefe, Lesego Cecilia (Rhodes University, Faculty of Science, Department of Chemistry, 2010)
This thesis presents a first ever extensive analysis of pesticides in water and sediments from the Okavango Delta, Botswana, employing green sample preparation techniques that require small volumes of organic solvents hence generating negligible volumes of organic solvent waste. Pesticides were extracted and pre-concentrated from water by solid phase extraction (SPE) and headspace solid phase microextraction (HS-SPME) while supercritical fluid extraction (SFE) and pressurized fluid extraction (PFE) were employed for sediments. Subsequent analysis was carried out on a gas chromatograph with electron capture detection and analytes were unequivocally confirmed by high resolution mass spectrometric detection. Hexachlorobenzene (HCB), trans-chlordane, 4,4"²-DDD and 4,4"²-DDE were detected after optimized HS-SPME in several water samples from the lower Delta at concentrations ranging from 2.4 to 61.4 Î¼g L-1 that are much higher than the 0.1 Î¼g L-1 maximum limit of individual organochlorine pesticides in drinking water set by the European Community Directive. The same samples were cleaned with ISOLUTE C18 SPE sorbent with an optimal acetone/n-hexane (1:1 v/v) mixture for the elution of analytes. No pesticides were detected after SPE clean-up and pre-concentration. HCB, aldrin and 4, 4"Ÿ-DDT were identified in sediments after SFE at concentration ranges of 1.1 - 30.3, 0.5 "“ 15.2 and 1.4 "“ 55.4 Î¼g/g, respectively. There was an increase of pesticides concentrations in the direction of water flow from the Panhandle (point of entry) to the lower delta. DDE, fatty acids and phthalates were detected after PFE with optimized extraction solvent and temperature. The presence of DDT metabolites in the water and sediments from the Okavango Delta confirm historical exposure to the pesticide. However their cumulative concentration increase in the water-flow direction calls for further investigation of point sources for the long-term preservation of the Delta. The green sample preparation techniques and low toxicity solvents employed in this thesis are thus recommended for routine environmental monitoring exercises.
Keywords: Water quality -- Botswana -- Okavango Delta; Water -- Analysis Pesticides -- Environmental aspects -- Botswana -- Okavango Delta; Water -- Pollution -- Botswana -- Okavango Delta; DDT (Insecticide) -- Environmental aspects -- Botswana -- Okavango Delta